ANALISIS PEMBAGIAN PERAN GENDER DALAM KELUARGA DI KELURAHAN BANJAR SERASAN KECAMATAN PONTIANAK TIMUR - Yani, Yani; Ulfah, Maria; Hidayah, Riama Al (Universitas Tanjungpura, 2023)
This research aimed to explore the distribution of gender roles within households in the village of Banjar Serasan RT 002 RW 002 in East Pontianak. Using a descriptive qualitative approach, we conducted ten semi-structured interviews with married couples who were employed outside the home. Our analysis found that while there was still a traditional division of labor where men worked outside the home and women took care of domestic responsibilities, many couples had negotiated new arrangements where both partners contributed to earning income and sharing household duties. These changes seemed to be driven by increased access to education and job opportunities as well as shifting cultural attitudes towards gender roles. We conclude that gender roles continue to evolve and adapt over time, but further efforts should be made to promote greater equality and flexibility in the distribution of domestic and paid work among all members of society.